Diffusion simulation of innovative products based on Lotka-Volterra. Issue 2 (18th September 2020) - Li, Chunfa; Wang, Shengkai; Tao, Jianqiang
Abstract : Purpose: In view of the particularity of innovative product diffusion under the background of market competition, this paper firstly uses consumer behavior theory to logically deduce the dynamic process of consumer behavior from the perspective of experience theory. Design/methodology/approach: Bass and Lotka-Volterra model are used to describe and model the consumers' perceptual behavior in competitive environment. On this basis, interactive modeling technology is used to model and simulate the diffusion process of innovative products. Finally, the validity of the model is verified by comparing two scenarios with an example. Findings: The research shows that the stronger the enterprise's competitiveness, the higher the market share of innovative products, and the positive impact on consumer perceived value, consumer perceived value can promote consumers' second purchase behavior. Positive word-of-mouth and advertising positively affect consumers' purchasing decisions; negative word-of-mouth negatively affects consumers' purchasing decisions. Originality/value: The interaction modeling technology and AnyLogic software platform are used to simulate the complexity of consumers' experiential perception so as to build the interaction and competition mechanism among different Agent, which realizes the dynamic simulation of the diffusion process of innovative products. This study provides guidance for enterprises to formulate effective marketing strategies.